1981
DOI: 10.2136/sssaj1981.03615995004500050009x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Mycorrhizal Infection in Soybeans

Abstract: Infection of soybean [Glycine max (L.) Merr.] roots by the vesicular‐arbuscular mycorrhizal fungus Glomus fasciculatus (Thaxt. sensu Gerd.) Gerd. and Trappe was assessed throughout the ontogeny of the symbiotic association. Degree of infection was evaluated by a histological method as percent infection and colorimetrically as mg chitin/g mycorrhiza. Correlation of data by the two methods was highly significant (r = 0.99) below 60% infection and not significant (r = 0.62) at higher levels. Assessment of infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
7

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 0 publications
0
22
0
7
Order By: Relevance
“…In this context glucosamine yield, which is related to fungal biomass may be more appropriate. Bethlenfalvay, Pacovsky and Brown (1981) reported that the amount of chitin in roots was highly significantly correlated with the percentage of the root length infected up to about 60 % infection, if intensity of infection was taken into account. Above this level the two methods were not in such good agreement due possibly to the difficulty in estimating visually the intensity at high levels of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this context glucosamine yield, which is related to fungal biomass may be more appropriate. Bethlenfalvay, Pacovsky and Brown (1981) reported that the amount of chitin in roots was highly significantly correlated with the percentage of the root length infected up to about 60 % infection, if intensity of infection was taken into account. Above this level the two methods were not in such good agreement due possibly to the difficulty in estimating visually the intensity at high levels of infection.…”
Section: Discussionmentioning
confidence: 99%
“…O crescimento das mudas foi acompanhado por 10 meses e avaliado por meio das variáveis resposta massa de matéria seca da parte aérea (MSPA), da parte radicular (MSR) e total (MST), após essas atingirem peso constante em estufa de secagem a 60 °C, com circulação de ar forçada. Quanto às variáveis microbiológicas, foram avaliadas: colonização micorrízica pelo método descrito por Phillips e Haymann (1970), sendo estimada pelo método de interseção em placa quadriculada (Giovanetti e Mosse, 1980); intensidade micorrízica, avaliada utilizando-se 10 segmentos de raízes, que foram dispostos em lâminas de microscopia, atribuindo-se notas de 0 a 100, conforme a ocupação da área radicular pelos fungos (Bethlenfalvay et al, 1981); densidade de esporos de FMAs, usando o método de peneiramento úmido descrito por Gerdemann e Nicolson (1963) em 50 mL de amostra do solo; e comprimento de micélio extrarradicular total, pelo método de Melloni e Cardoso (1999), utilizando-se de lavagem de amostras do solo em água de torneira, seguido de agitação, filtração a vácuo em membrana quadriculada e visualização em microscópio óptico em luz comum. Calculou-se a dependência micorrízica das plantas, utilizando a fórmula proposta por Planchette et al (1983): 100 × [(A-B)/A], em que A representa a massa de matéria seca das plantas micorrizadas; e B, a massa de matéria seca das plantas não micorrizadas.…”
Section: Methodsunclassified
“…The content of chitin used as a measure of endomycorrhizal colonization was determined according to Bethlenfalvay, Pacovsky & Brown (1981). Three different nutrient solutions containing either 1 mM KNO3, 1 niM Asp or 1 mM Ser as the N source with 0-137 mM phosphate, pH 6, and other macroand micro-nutrients as described pre\'iously by Laine*?/ al.…”
Section: Plant and Fungus Materialsmentioning
confidence: 99%